Immunohistochemical evidence from co-localization and denervation studies for four types of substance P-containing nervous structures in the rat superior cervical ganglion - Heym, Christine; Common, Bernd; Klimaschewski, Lars Peter; Preissler, Ulrike; Kummer, Wolfgang (Anatomy and embryology, 1993)
Four types of substance P-immunoreactive structures have been distinguished in the rat superior cervical ganglion by double-immunofluorescence microscopy: (1) A major population of mainly varicose fibres enmeshed singly-scattered neuronal perikarya, some of which contained vasoactive intestinal polypeptide-immunoreactivity. These substance P-immunoreactive fibres did not contain colocalized calcitonin gene-related peptide (CGRP) and were absent after transection of the cervical sympathetic trunk. (2) A rather small substance P-immunoreactive fibre population with colocalized calcitonin gene-related peptide-immunoreactivity was distributed in a patchy manner and disappeared after cutting the postganglionic branches. (3) Most of the intraganglionic small intensely fluorescent (SIF) cell clusters were intensely substance P-immunoreactive. SIF cells were not visibly changed in number and fluorescence intensity by either surgical procedure. (4) Immunoreactivity was not visible in principal ganglionic neurons of control ganglia, but occurred in cell bodies after pre- as well as after postganglionic nerve transection. Some of the substance P-immunolabelled perikarya in addition revealed immunostaining to antisera against the catecholamine-synthesizin enyzme tyrosine hydroxylase or against the neuropeptides leu-enkephalin and vasoactive intestinal polypeptide, respectively. The results strongly suggest that, in addition to a substance P-containing preganglionic input (1), and a supply by substance P-containing sensory axon collaterals (2), the superior cervical ganglion of the rat gives origin to a paraganglionic (3) and a postganglionic (4) substance P-immunoreactive intrinsic system, the latter becoming visible only after disconnection of the sympathetic pathway.